(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The tourism industry is currently making enormous financial gains. This extends to medical tourism, which is the phrase for the global use of health care services, in addition to hotels, restaurants, and historical sites. The global market for healthcare services and medical tourism is expanding quickly. It is a fusion of two economic activities, or the blending of the tourism and medical industries. The huge demand for high-quality healthcare services at reasonable prices has recently drawn foreign travellers to emerging nations like India, who have the necessary resources, skilled medical professionals, employees, and facilities to meet these demands. With the aid of data analysis, this research focuses on the benefits of medical tourism in Andhra Pradesh and examines the variables that affect people’s decisions to make Andhra Pradesh as the choice of destination for medical treatment. The study also identifies the elements which influence the choice of destination (Hospital) for Medical Tourism in Andhra Pradesh.